(3GdJTQjYGJ GdeGdjI h GdeUQajIaj GdCQOf (B/s - (3GdQTjOGJ, eeOhM eMeOs ((3YeGf(B: s (3OGQ hGFd(B, s, 2004)
(3GdHfc GdeQcRj h GdHfhc GdJLGQjI eY ChLg GdQbGHI Ydi fTGWGJ GdHfc NGUI MSH bGfhf GdHfhc dYGe (B2000(3, GdLhGfH GdbGfhfjI dCYeGd GdHfc GdeQcRj h GdJfXje GdbGfhfj dCYeGd GdeDSSGJ GdeGdjI GdeJNUUI h cPdc GdLhGfH GdbGfhfjI dGYeGd GdHfc GdeQcRj HJfGhd cd ef GdhOGFY GdeUQajI , GdMSGH GdLGQj , GdGYJeGO GdeSJfOj , NWGH GdVeGf GjLGQ GdNRGFf GdMOjOjI , HWGbGJ GdGJeGf h GdNUe h GdLhGfH GdbGfhfjI ddeDSSGJ GdeGdjI HJfGhd Yed GdShb GdeGdj , GdGhQGb GdeGdjI , GdGYeGd GdeUQajI , GdYedGJ GdGLfHjI h CNjQG GdGSJKeGQ h JTLjYg (B.s
Keywords: (3GdHfhc `` JTQjY `` GdGQOfs; (3GdeGdjI `` JTQjY ` GdGQOfs